Libraries and sustainability programs and practices for community impact - Aldrich, Rebekkah Smith; Antonelli, Monika; Ho, Adrian K. 1969-; Tanner, René 1963- (ALA Editions, 2022)
"This book explores a sustainability lens through which operational and outreach decisions can be made, discusses why sustainability matters to libraries and their communities, shares real-life examples of sustainability programming, and provides recommendations from library workers who have been active in putting sustainability into practice"--